2017
DOI: 10.1073/pnas.1706693114
|View full text |Cite
|
Sign up to set email alerts
|

Harm to self outweighs benefit to others in moral decision making

Abstract: How we make decisions that have direct consequences for ourselves and others forms the moral foundation of our society. Whereas economic theory contends that humans aim at maximizing their own gains, recent seminal psychological work suggests that our behavior is instead hyperaltruistic: We are more willing to sacrifice gains to spare others from harm than to spare ourselves from harm. To investigate how such egoistic and hyperaltruistic tendencies influence moral decision making, we investigated trade-off dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 22 publications
(39 reference statements)
6
33
0
Order By: Relevance
“…However, it is worth highlighting that the bias in this direction seems to appear only in a very narrow set of conditions (i.e., only when judging whether the sacrifice is wrong) and is probably less common than would be expected. This is in line with recent findings of low willingness to undergo harm for benefit of others in laboratory settings (Volz, Welborn, Gobel, Gazzaniga, & Grafton, 2017). Additionally, in accordance with the results of previous studies (e.g., Ditto, Pizarro, & Tannenbaum, 2009;Huebner & Hauser, 2011;Valdesolo & DeSteno, 2007;, in Study 2 we also observed the much more common self-serving bias, especially when participants judged whether the sacrifice is right and whether it should not be done.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is worth highlighting that the bias in this direction seems to appear only in a very narrow set of conditions (i.e., only when judging whether the sacrifice is wrong) and is probably less common than would be expected. This is in line with recent findings of low willingness to undergo harm for benefit of others in laboratory settings (Volz, Welborn, Gobel, Gazzaniga, & Grafton, 2017). Additionally, in accordance with the results of previous studies (e.g., Ditto, Pizarro, & Tannenbaum, 2009;Huebner & Hauser, 2011;Valdesolo & DeSteno, 2007;, in Study 2 we also observed the much more common self-serving bias, especially when participants judged whether the sacrifice is right and whether it should not be done.…”
Section: Discussionsupporting
confidence: 93%
“…The money and shock terms are scaled by a harm aversion parameter ( κ ) that quantifies the exchange rate between money and pain and takes on different values for pain to self and others. Strikingly, across several studies harm aversion for others was consistently greater on average than harm aversion for self (Crockett et al., , , ), an effect that has been replicated by an independent research group using a different paradigm (Volz, Welborn, Gobel, Gazzaniga, & Grafton, ). People were willing to pay more to prevent shocks to others than to themselves, and required more compensation to increase shocks to others than themselves; that is, their behavior was “hyperaltruistic” (Kitcher, ).…”
Section: Harm Aversion As a Core Component Of Moral Cognition Across mentioning
confidence: 90%
“…Next, both the ramping and rating stages were repeated to verify that we had accurately identified the participant's pain tolerance. Finally, the pain ratings and shock intensities from the second rating procedure were fit with a sigmoid function to model the relationship between shock intensity and perceived pain for this individual [33]. Based on this sigmoid function, we identified the shock intensity that predicted a pain rating of 8 out of 10.…”
Section: Experimental Designmentioning
confidence: 99%
“…where r offer is the available reward, s offer is the contingent shock, β r and β s describe how strongly the individual subject weights rewards and shocks, and β 0 is the individual's intercept, indicating their intrinsic motivations to pursue reward versus avoid shock (33). We separately modeled each participant's choice data with logistic regression, a specialized from of the generalized linear model, using the glm package in R. Offers to which participants failed to respond before the decision deadline were repeated at the end of the task.…”
Section: Behavioral Statistical Analysismentioning
confidence: 99%